IMPLEMENTASI PERATURAN DAERAH KOTA TASIKMALAYA NOMOR 7 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH DALAM PERSPEKTIF SIYASAH SYAR’IYYAH (Suatu Penelitian di Dinas Lingkungan Hidup Kota Tasikmalaya) - Wimpi U Rohman, Litra (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
The background to the waste management policy is the high amount of waste generation in the City of Tasikmalaya. Garbage is something that is always there in everyday life. All those who are active will definitely produce waste as a result of these activities is the increased production of waste generated by the community. To deal with this problem, the Regional Government of Tasikmalaya City issued a Regional Regulation on Waste Management Number 7 of 2012 concerning Waste Management which aims to improve professional waste management so that a clean environment is created and waste is a resource. The aims of this study are: 1) To find out the role of the Environmental Service in waste management based on Regional Regulation of the City of Tasikmalaya Number 7 of 2012 concerning Waste Management. 2) To find out what factors are inhibiting and supporting the implementation of waste management policies based on Regional Regulation Number 7 of 2012 concerning Waste Management. 3) To find out the policies after the issuance of Regional Regulation Number 7 of 2012 concerning Waste Management by Government Apparatuses. 4) To find out the implementation of the Tasikmalaya City Regional Regulation Number 7 of 2012 concerning Waste Management in the Siyasah Syar'iyyah Perspective. The method used in this research is normative juridical and empirical approach. The results of this study indicate that the implementation of waste management policies has not been fully successful in reducing the amount of existing waste generation. In its implementation there are still various obstacles such as, lack of human resources, infrastructure, budget and public awareness. Recommendations that can be given for this problem include socializing local regulations to the community, adding human resources and infrastructure and conducting coaching and training to the people of Tasikmalaya City